(untitled) (Sociologisk Forskning, 2007)
The power of homosociality: how young men “do” masculinity in groups and individually Using young men’s narratives, about other men, friends, dates and girlfriends, this article discusses the following questions: Can the interpretation – the understanding of young men’s collective presentations of masculinity as a surface that hides a more complex masculinity – undermine how we interpret young men’s talk about and interaction with other men, as well as with women? Can this disassembling understanding have an impact on how young men interpret and relive the interactions with other men, as well as with women? Can this disassembling of the homosocially created masculinity from the more individually created masculinity shape secondary gains for the young men, such as e.g. a more flexible and stretchable arena of responsibility, as well as more flexible space of acting? Thomas Johansson, Professor of Social Work social work, states that if we only focus the homosocially created masculinity, this will reshape a less nuanced picture of young men’s way of doing masculinity (Johansson 2005). Thus, young men’s vulnerability and difficulties remain hidden. However, this disassembling of the homosocially created masculinity from the more individually based doings of masculinity could possibly also give secondary gains, such as e.g. a more flexible and stretchable field of responsibility, as well as more flexible space of acting. This article shows that using a fragmentised and situated masculinity, as a way of understanding the complexity and the ambivalence in young men’s project of doing masculinity, makes evident – on the one hand – the vulnerability in young men’s process of doing masculinity. On the other hand, however, this view also makes it possible for young men to avoid responsibility for their actions. Instead the situated context – e.g. if in a peer group or alone, and what kind of relations the young man has – will be significant for how the act will be interpreted. The empirical material consists of six individual interviews and one group interview with four men. The age span of the participants is 16 to 24 years old. The overall theme for the discussions is heterosexual practice and relations.